Evaluation of the effects of the health subsidy focalization policy on the population without (2003)
Objectives: To analyze the problems of the focalization policy and the characteristics of decisionmaking to assign health subsidies for the population of Sisben levels 3 and 4 of 4 localities in Bogotá, in order to propose criteria for transforming the processes of policy formulation and correct its defects on marginalization and exclusion. Methods: A critical, participative and pluralist methodological approach, which combined multiple research methods and techniques from a systemic and post-estructuralist perspective, was undertaken. For sub-projects were carried out. The subsidy-focalization policy in Colombia was analyzed based unpon the arguments of the main socio-political actors who participated in its formulation. In order to establish how the focalization policy of health spending is perceived by the excluded population, the public providers and the local authorities, a qualitative study was done based upon focal groups and in-depth interviews. A follow-up of the accessibility to and use of health services was also carried out from the definition of a tracing condition. Finally, collective  recommendations of policies were formulated from the perspective of the excluded population, the providers and the authorities. Results: The problems of a focalization policy, product of the adoption of a narrow and utilitarian concept of poverty and social justice, of a scarcely participative process of analysis and measurement of poverty, of the screening and setup of the programs and of the evaluation of the results of the policy, are identified. Conclusions: Measures to facilitate and make health care accessibility more equalitarian are justified not only because of poverty, but also because of the correction of inequities in health which result from other determinants that can deepen inequalities, marginalization and exclusion. The adoption of a broad approach for analyzing poverty, for decision-making and for social participation is proposed.